2017
DOI: 10.1371/journal.pgen.1006921
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Caenorhabditis elegans orthologs of human genes required for mitochondrial tRNA modification cause similar electron transport chain defects but different nuclear responses

Abstract: Several oxidative phosphorylation (OXPHOS) diseases are caused by defects in the post-transcriptional modification of mitochondrial tRNAs (mt-tRNAs). Mutations in MTO1 or GTPBP3 impair the modification of the wobble uridine at position 5 of the pyrimidine ring and cause heart failure. Mutations in TRMU affect modification at position 2 and cause liver disease. Presently, the molecular basis of the diseases and why mutations in the different genes lead to such different clinical symptoms is poorly understood. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…Defects in tRNA modifications and modification enzymes are associated with oxidative stress [ 40 ] and human diseases including cancer, diabetes and cardiomyopathy [ 38 ]. Indeed, results from a recent study in Caenorhabditis elegans associating defects in post-transcriptional modification of mitochondrial tRNAs with dysfunctional oxidative phosphorylation suggest that the cell's maladaptive response to hypomodified mitochondrial tRNAs may be a mechanism underlying disease development [ 41 ]. Although speculative, the idea that exposure to the space environment may lead to aberrant tRNA post-transcriptional modifications is provocative and warrants further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Defects in tRNA modifications and modification enzymes are associated with oxidative stress [ 40 ] and human diseases including cancer, diabetes and cardiomyopathy [ 38 ]. Indeed, results from a recent study in Caenorhabditis elegans associating defects in post-transcriptional modification of mitochondrial tRNAs with dysfunctional oxidative phosphorylation suggest that the cell's maladaptive response to hypomodified mitochondrial tRNAs may be a mechanism underlying disease development [ 41 ]. Although speculative, the idea that exposure to the space environment may lead to aberrant tRNA post-transcriptional modifications is provocative and warrants further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate a possible role of mt-ELP3 in modifying mt-tRNAs, we analyzed the sensitivity to digestion with the tRNA-specific RNase angiogenin of mt-tRNA Glu , mt-tRNA Lys and mt-tRNA Leu (with the τm5U modification) and mt-tRNA Val (without the τm5U modification) from control cells and from cells overexpressing mt-ELP3. tRNAs lacking modification at the wobble position are more sensitive toward angiogenin-mediated digestion than the corresponding modified tRNAs (Lefkimmiatis et al, 2019) (Navarro-González et al, 2017)(R. Boutoual et al, 2018). After in vitro angiogenin digestion of total RNA purified from control cells and cells overexpressing mt-ELP3, the digested products were analyzed using northern blot analysis with a specific digoxigenin (DIG)-labeled oligodeoxynucleotide probe for the mentioned mt-tRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…This approach was based on previous findings indicating that loss of the U34 modification at position 5 increases the angiogenin-mediated cleavage of the E. coli tRNA Lys , which is a substrate for the MTO1 and GTPBP3 bacterial orthologs 18 . This qualitative approach has proven to be useful in analysing the modification status of mt-tRNAs obtained from GTPBP3 knocked-down cells 18 and Caenorhabditis elegans strains carrying a deletion mutation in the GTPBP3 or MTO1 homolog 17 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons why TRMU and GTPBP3 or MTO1 mutations produce different clinical outcomes is currently unknown. We have proposed that these defects affect retrograde signalling from mitochondria to nucleus in a different manner, which results in different tissue-dependent nuclear responses and, consequently, in different phenotypes 17 . In this respect, we have reported that stable silencing of GTPBP3 triggers an AMPK-dependent retrograde signalling pathway, which down-regulates the mitochondrial pyruvate carrier (MPC), while up-regulating the expression of the uncoupling protein 2 (UCP2) and genes involved in glycolysis and fatty acid oxidation 18 .…”
Section: Introductionmentioning
confidence: 99%